Skin Cancer Management A Practical Approach - MacFarlane, Deborah.; MacFarlane, Deborah. (Springer New York : Imprint: Springer, 2010)
The incidence of skin cancer continues to rise, as do the challenges physicians face in treating the growing population of skin cancer patients. Skin Cancer Management: A Practical Approach addresses the spectrum of skin cancers from the precancerous to the inoperable. A wide selection of medical treatments and surgical procedures are described in detail and supplemented with an abundance of full-color figures. Numerous case studies help to illustrate the various techniques. Additional highlights of the book include: discussion of potential complications and their management in each chapter one-of-a-kind chapters on radiologic imaging of head and neck skin cancer, management of skin cancer in skin of color, and intralesional and perilesional treatment of skin cancers boxed insets that emphasize the most important clinical facts authorship by the leading experts in the field. Skin Cancer Management: A Practical Approach covers the state-of-the art in skin cancer treatment with concision and clarity. This highly informative book is a one-stop resource for the physician looking to make the best possible choices in their daily practice.